1990
DOI: 10.1111/j.1365-2958.1990.tb00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of phosphate transport in Escherichia coli

Abstract: Escherichia coli transports inorganic phosphate (Pi) by the low-affinity transport system, Pit. When the level of the external Pi is lower than 20 microM, another transport system, Pst, is induced with a Kt of 0.25 microM. An outer-membrane porin, PhoE, with a Km of about 1 microM is also induced. The outer membrane allows the intake of organic phosphates which are degraded to Pi by phosphatases in the periplasm. The Pi-binding protein will capture the free Pi produced in the periplasm and direct it to the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(139 citation statements)
references
References 38 publications
3
134
0
2
Order By: Relevance
“…Kinetic analysis has shown that Pi uptake occurs in a bi-phasic manner, and consists of high-affinity (K m 1-10 µM) and low-affinity (K m 100-1000 µM) uptake mechanisms in plants (Clarkson, 1984), bacteria (Rao & Torriani, 1990), yeast (Borst-Pauwels, 1981) and other fungi (Burns & Beever, 1977), including germ tubes of the mycorrhizal fungus, Gigaspora margarita (Thomson et al, 1990).…”
Section: mentioning
confidence: 99%
“…Kinetic analysis has shown that Pi uptake occurs in a bi-phasic manner, and consists of high-affinity (K m 1-10 µM) and low-affinity (K m 100-1000 µM) uptake mechanisms in plants (Clarkson, 1984), bacteria (Rao & Torriani, 1990), yeast (Borst-Pauwels, 1981) and other fungi (Burns & Beever, 1977), including germ tubes of the mycorrhizal fungus, Gigaspora margarita (Thomson et al, 1990).…”
Section: mentioning
confidence: 99%
“…The Pst system of P. mirabilis (Table 1), a multimeric, high-affinity inorganic phosphate (P i ) transporter, is induced at limiting extracellular P i concentrations (,1 mM, K app m of 0.2 mM) (Rao & Torriani, 1990;Rosenberg et al, 1977). pst mutants are highly attenuated in cochallenge colonization of the CBA mouse model (Burall et al, 2004;Jacobsen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Crystal formation occurs due to the urease-catalysed hydrolysis of urea into ammonia, leading to an increase in the local pH and the precipitation of calcium, magnesium and phosphate ions (Morris et al, 1999). The pathogenesis of P. mirabilis UTIs is not at present understood fully.The Pst system of P. mirabilis (Table 1), a multimeric, high-affinity inorganic phosphate (P i ) transporter, is induced at limiting extracellular P i concentrations (,1 mM, K app m of 0.2 mM) (Rao & Torriani, 1990;Rosenberg et al, 1977). pst mutants are highly attenuated in cochallenge colonization of the CBA mouse model (Burall et al, 2004;Jacobsen et al, 2008).…”
mentioning
confidence: 99%
“…Our work has clearly shown that OPH is a lipoprotein, and adds to a growing list of Tat-dependent lipoproteins in bacteria and archaea (20,44,47,48). Interestingly, OPH contains an alanine residue at the ϩ2 position and according to the sorting rules for E. coli lipoproteins (42) should be translocated to the outer The other components of the ABC-type phosphate acquisition system (PstA, PstB, and PstC) for which PstS is the periplasmic binding protein are also shown.…”
Section: Discussionmentioning
confidence: 99%
“…From the list of proteins, subunits of the F 1 F o -ATP synthase (␣, ␤, ␥), the phosphate ABC transporter substrate-binding protein (PstS) and efflux pump components AcrB and TolC were identified as candidate OPH interacting partners (Table 3). It is interesting to note that the identified peptides matched with proteins involved either in phosphate uptake (44) or in effluxing of xenobiotics (45), as organophosphates are xenobiotics that also contain a potential source of phosphate.…”
Section: C24smentioning
confidence: 99%